THE EFFECT OF USING COMPUTER ASSISTED LANGUAGE LEARNING (CALL) METHOD ON STUDENTS’ LISTENING SKILL AT THE SEVENTH GRADE STUDENTS OF SMP NEGERI 3 STABAT - Ummi Umara; Ika Lestari (Jurnal Serunai Bahasa Inggris, 2020)
Applying an appropriate teaching method plays an important role in the teaching or learning process including teaching listening as a skill. The listening skill is one of the four most important and difficult skill to be taught in English. Students are facing a difficulty either in understanding native speaker or in producing native-like English (accent/pronunciation). They are also unprepared to function in the new word. And then, in most class students are unmotivated and act as passive listeners. This study aimed to find out whether using computer assisted language learning (CALL) method affect listening skill. In this study, using computer assisted language learning (call) method as the independent variable (X) and students’ listening skill as the dependent variable (Y), with the hypothesis: using computer assisted language learning (CALL) method affects on students’ listening skill of seventh year students of SMP NEGERI 3 STABAT  at academic year 2018/2019. The population of this study was seventh year students of SMP NEGERI 3 STABAT at academic year 2018/2019, which consisted of 185 students. The sample was taken by using random sampling technique, the total sample  was 60 students. Then, the sample was divided into two groups, the group taught by using computer assisted language learning (CALL) was as the experimental group and the group taught without computer assisted language learning (CALL) was as the control group. The  writer used test as the instrument of collecting data. The data was analyzed by using t-test formula. Based on the data analysis, it was found that the value of t-observed (to) was higher than the value of t-table, (tobserved = 8,39 > ttable = 1.67). Therefore, the hypothesis proposed by the writer was accepted. In the other words, using computer assisted language learning (CALL) affects listening skill of seventh year students of SMP NEGERI 3 STABAT at academic year 2018/2019.